Growth and anemia among children with tuberculosis infection at different sites in Southwest China - Gao, Zhongmin; Liu, Quanbo; Deng, Qin; Kong, Lin; Liu, Yongfang (Frontiers in Pediatrics, 2023)
Objectives To explore the effects of tuberculosis (TB) infection at different sites on anthropometric indicators, malnutrition and anemia incidence in children in Southwest China. Methods From January 2012 to December 2021, a total of 368 children aged 1 month to 16 years were enrolled. According to the sites of TB infection, they were divided into three groups: tuberculous meningitis (T group), tuberculous meningitis complicated withpulmonary tuberculosis (TP group), and tuberculous meningitis complicated with pulmonary tuberculosis and abdominal tuberculosis (TPA group). Data on weight, height, nutritional risk, blood biochemical indicators and basic descriptions were collected within 48 h after admission. Results The body mass index-for-age z score (BAZ), height-for-age z score (HAZ), and concentrations of hemoglobin (Hb) and albumin (ALB) decreased in the following order: T group, TP group, and TPA group. The prevalence of malnutrition was the highest in the TPA group (69.5%, 82/118) and 10-to 16-year-old group (72.4%, 63/87). Children aged 0.5–2 years exhibited the highest anemia prevalence of 70.6% (48/68) among the four age groups.The TPA group had the highest incidence of anemia (70.5%, 67/95) compared to T group and TP group.Compared with the treatment group, the abandonment group had a lower BAZ, HAZ and levels of HB and ALB, a higher rate of severe malnutrition, and higher nutritional risk scores. Children who had a low BAZ [odds ratio (OR) = 1.98], nutritional risk (OR = 0.56) and anemia (OR = 1.02) were less likely to obtain treatment with their guardians' support. Conclusions Children with tuberculous meningitis were at risk for growth disorders and anemia, especially when complicated with pulmonary tuberculosis and abdominal tuberculosis. The prevalence of anemia and malnutrition was the highest among patients aged 1 month to 2 years and 10–16 years, respectively. Nutritional status was one of the causes of abandoning treatment.